1999
DOI: 10.1007/bf03391973
|View full text |Cite
|
Sign up to set email alerts
|

Is the learn unit a fundamental measure of pedagogy?

Abstract: We propose a measure of teaching, the learn unit, that explicitly describes the interaction between teachers and their students. The theoretical, educational research, and applied behavior analysis literatures all converge on the learn unit as a fundamental measure of teaching. The theoretical literature proposes the construct of the interlocking operant and embraces verbal behavior, social interaction, and translations of psychological constructs into complex theoretical respondent-operant interactions and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
110
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 41 publications
0
110
0
Order By: Relevance
“…The learn unit is an experimentally tested type of instructional trial that has been shown to be an efficient instructional procedure (Albers & Greer, 1991;Bahadourian, Tam, Greer, & Rousseau, 2006;Emurian, 2004;Emurian, Hu, Wang, & Durham, 2000;Greer & Hogin-McDonough, 1999;Hogin, 1996;Selinske, Greer, & Lodhi, 1991). The characteristics of the learn unit were suggested in Skinner's (1968) programmed instruction frame.…”
Section: Identified Sources Of Namingmentioning
confidence: 99%
“…The learn unit is an experimentally tested type of instructional trial that has been shown to be an efficient instructional procedure (Albers & Greer, 1991;Bahadourian, Tam, Greer, & Rousseau, 2006;Emurian, 2004;Emurian, Hu, Wang, & Durham, 2000;Greer & Hogin-McDonough, 1999;Hogin, 1996;Selinske, Greer, & Lodhi, 1991). The characteristics of the learn unit were suggested in Skinner's (1968) programmed instruction frame.…”
Section: Identified Sources Of Namingmentioning
confidence: 99%
“…In a series of experiments designed to test the components of tutoring that lead to learning on the part of the tutor (Greer et al, 2004), Greer et al experimentally tested for the presence or absence of operants for the tutors prior to the tutors engaging in peer tutoring. In these studies, the tutors used learn-unit presentations (Albers & Greer, 1991;Bahadourian, Tam, Greer, & Rosseau, 2006;Emurian, 2004;Emurian, Hu, Wang, & Durham, 2000;Greer, 1994aGreer, ,1994bGreer, , 2002Greer & McDonough, 1999;Ingham & Greer, 1992) to tutor peers. Learn units are instructional presentations that include components of instruction that are deemed necessary, if not sufficient, conditions for learning (Greer, 1994a).…”
mentioning
confidence: 99%
“…That is, in the studies comparing percentage mastery versus fast rate mastery, inevitably the participants who received rate instruction also received more instructional presentations. Recently, investigators have isolated the instructional unit that predicts learning, the learn unit (Albers & Greer, 1991 ;Emurian, Hu, Wang , & Durham , 2000;Emu rian , 2004;Greer & McDonough, 1999;Greer, McCorkle, & Williams, 1989;Ingham & Greer, 1992;Selinske, Greer, & Lodhi , 1991). A learn unit includes the teacher or automated teaching device ensuring the student's attention, the unambiguous delivery of an antecedent that is to be the discriminative stimulus when the student has mastered the discriminated operant, and delivery of either a reinforcer or a correction .…”
mentioning
confidence: 99%